Empirically tested indigenous supply chain resilient framework for future businesses - Offei, Martin Otu; Toku, Lomatey; Akrofi, Thomas; Adelwini, Bugri Benjamin; Shere, Jayadatta (Journal of Accounting, Business and Finance Research, 2025)
The issues of resilience contribute significantly to a sustainable supply chain of goods and services coming through the main ports of entry and this is crucial for the survival of many industries, organizations and customers in the World, the African continent and the Sub-Sharan region. Thus, sustainable supply chains rely heavily on information communications technologies (ICT) to perform their operations. The resilience of these ICT processes ensure that these goods and services are delivered to satisfy customers without compromising quality. The ICT that enables the sustainable supply chain performance has to be responsive, reliable and efficient. This quantitative study of two hundred and fifty (250) respondents investigates the influence of ICT (agility, reliability and efficiency - ICTARE) on economic sustainable supply chain performance (ESSCP) and the mediated effect of robust competence of IT staff between ICTARE and ESSCP. Lisrel 8.0 was used to analyze the data obtained from the respondents. The study results suggest a positive relationship between ICTARE and ESSCP. The results also confirm a full mediation between ICT reliability and sustainable supply chain performance through ICT staff competence within the context of shipment of goods and services within Ghana’s ports and harbours. The implication of this research is enormous: ICT used in a suitable way will enhance the resilience of supply chain networks in supporting the distribution of goods and ‘services in a timely manner’ in order to improve customer satisfaction.